2016
DOI: 10.1016/j.jtcvs.2016.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes and length of stay: A firm grasp of the obvious?

Abstract: Intraoperative adverse events can be compensated by technical performance in neonates and infants after cardiac surgery: a prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…Our finding in the present study also indicated that neonatal mortality was also related to the length of hospital stay, gestational age and birth weights of the newborn. This finding is in line with other studies 33,34. The lower the gestational and birth weight the higher chance of death and this is due to the fact that underweight and preterm newborn had immaturity of immune systems and other body defense mechanisms which control newborn disease susceptibility 1.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding in the present study also indicated that neonatal mortality was also related to the length of hospital stay, gestational age and birth weights of the newborn. This finding is in line with other studies 33,34. The lower the gestational and birth weight the higher chance of death and this is due to the fact that underweight and preterm newborn had immaturity of immune systems and other body defense mechanisms which control newborn disease susceptibility 1.…”
Section: Discussionsupporting
confidence: 91%
“…Being born preterm was found to raise the likelihood of mortality. These are consistent with studies done in the country and abroad [26,29,33,41,44,46,[52][53][54][55][56]. This could be explained as Zage [57] described, the smaller the birth weight and the gestation the greater the chance of having neonatal death due to lung immaturity and immune systems linked with ELBW and extremely PTBs.…”
Section: Plos Onesupporting
confidence: 90%